2018
DOI: 10.1016/j.ejsobi.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Growth benefits provided by different arbuscular mycorrhizal fungi to Plantago lanceolata depend on the form of available phosphorus

Abstract: Strains of arbuscular mycorrhizal fungi (AMF) differ markedly in the growth benefits they provide to plants. We investigated whether these differences depend on the chemical form of inorganic phosphorus. The closely related AMF Glomus custos and Rhizophagus irregularis were compared using Plantago lanceolata as the host plant, grown in quartz sand with either soluble orthophosphate or sparingly soluble hydroxyapatite as a sole source of phosphorus. In a growth experiment with AMF-inoculated plants in a climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…First, we utilised apatite, a form of rock P that is difficult for plant roots to obtain directly, but that arbuscular mycorrhizal fungi can help break down (Reynolds et al ., 2006; Pel et al ., 2018). Our aim was to use a form of phosphorus that was difficult for the host to take up directly (Reynolds et al ., 2006; Pel et al ., 2018), essentially increasing the ‘bargaining’ position of the fungi (Noë & Kiers, 2018). Past work on split‐root systems has shown that root systems colonised with arbuscular mycorrhizal fungi are better able to take up of apatite compared with noncolonised roots (Whiteside et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we utilised apatite, a form of rock P that is difficult for plant roots to obtain directly, but that arbuscular mycorrhizal fungi can help break down (Reynolds et al ., 2006; Pel et al ., 2018). Our aim was to use a form of phosphorus that was difficult for the host to take up directly (Reynolds et al ., 2006; Pel et al ., 2018), essentially increasing the ‘bargaining’ position of the fungi (Noë & Kiers, 2018). Past work on split‐root systems has shown that root systems colonised with arbuscular mycorrhizal fungi are better able to take up of apatite compared with noncolonised roots (Whiteside et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Apatite is difficult for plant roots to dissolve directly, however arbuscular mycorrhizal fungi can help break down apatite (Reynolds et al ., 2006; Pel et al ., 2018). Past work has shown that arbuscular mycorrhizal fungi can increase the dissolution and uptake of apatite, even under sterile conditions when no other microbes are present (Reynolds et al ., 2006; Pel et al ., 2018; van’t Padje et al ., 2020). We constructed three colours of QD‐apatite (cyan (490 nm), yellow (576 nm) and red (666 nm)) that were equal in size and mass.…”
Section: Methodsmentioning
confidence: 99%
“…We tagged hydroxyapatite, a form of rock phosphate [ 44 , 45 ], with fluorescent nanoparticles. Specifically, we used two spectrally different carboxyl terminated quantum-dots (QDs) with 488 nm cyan and 666 nm red emission (Crystalplex, Pittsburg PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Past work has shown that arbuscular mycorrhizal fungi can increase the dissolution and uptake of apatite [63,64]. While the apatite uptake mechanism for arbuscular mycorrhizal fungi is still unknown, fungi generally use endocytic pathways to take up large particles [65][66][67].…”
Section: Discussionmentioning
confidence: 99%